Cytomorphological Spectrum of Orbital and Peri-orbital Lesions – A Retrospective Study from A Tertiary Care Center, Manipur, India - Singh, Yengkhom Daniel; Pukhrambam, Gayatri Devi; Shimray, Rachel; Laishram, Sharmila; Sarangthem, Babina; Persy, Haobijam; Akham, Ngamba; Khuraijam, Sushma (Annals of Pathology and Laboratory Medicine, 2024)
Background Fine needle aspiration cytology (FNAC) is a reliable, safe and simple diagnostic technique which is being implemented in diagnosing palpable and/or visible lesions in the body. This study was conducted for evaluating the role of FNAC as a routine screening/diagnostic tool in a spectrum of orbital and periorbital lesions. The aim of this study was to evaluate the role of FNAC in orbital and periorbital lesions. Methods A hospital based cross-sectional study was conducted in the Cytology section, Department of Pathology, RIMS for a period of 10 years from April 2013 to May 2022. A total of 95 cases with orbital and periorbital lesions were inducted in the study through purposive sampling. FNAC procedure was done using 10cc/20cc syringe with 23G/22G needle with or without a Cameco handle. Slides were stained using MGG (May-Grunwald Giemsa) and Pap (Papanicolaou) stains followed by their microscopic examination. Demographic parameters such as age and gender as well as clinical parameters such as size, site and duration of the lesion were analyzed. Result The mean age of patients was found to be 33 years with a slight male predominance (54 patients; 56.84%). The adequacy of FNAC was 96.82%. Epidermal Inclusion Cyst (30 cases; 31.58%) was the commonest lesion. Five cases (5; 5.26%) were malignant on cytopathology. By applying Kappa statistics, a near perfect agreement (k=0.86) between FNAC and histopathology was observed, being statistically significant, p=0.01 (<0.05). Conclusion: In our study, a high concordance/agreement was observed for the neoplastic lesions, thereby establishing FNAC as a useful tool for screening as well as diagnosing orbital and periorbital lesions. It surrogates other invasive procedures, eliminating complications in nonresectable or inapproachable lesions.